A political economy of niche-building: Neoliberal-developmental encounters in photovoltaic electrification in Kenya. (October 2018) - Byrne, Rob; Mbeva, Kennedy; Ockwell, David
Abstract: International agreements on energy access and climate change, formulated according to neoliberal orthodoxy, will drive significant finance to developing countries for clean technology investments. But critics call for more active state intervention – a developmental approach – arguing that free markets alone will not deliver what is required. This creates the potential for confrontation between contradictory ideologies in national policymaking and implementation: neoliberalism in global agreements versus developmentalism in national policy. The Kenyan photovoltaics (PV) market has long-experienced neoliberal-developmental policy interactions, reflecting on which can illuminate how such encounters might unfold in the future. We construct a new 'niche political economy' theoretical framework to analyse these past interactions, constituting one of three contributions we offer. The second is empirical, showing how PV practitioners, national policymakers and global development actors have negotiated their policymaking encounters over time. Our third contribution offers reflections on the issues explored, discussing what this might mean for future neoliberal-developmental encounters. We find that action on the ground will emerge from messy negotiated interactions between competing ideologies rather than be determined by powerful neoliberal actors. As such, realising global energy and climate ambitions becomes even more uncertain unless long-term active niche-building resources are secured in international agreements.